Telephone consults at the Infectious Disease Outpatient Clinic during the early period of the COVID-19 epidemic - Osanai, Yasuyo (Glob Health Med, 2020)
Once novel coronavirus disease 2019 (COVID-19) emerged in Wuhan, China in December 2019 and the first case in Japan was reported the following month, telephone inquiries to the Infectious Disease Outpatient Clinic increased. During the first wave of the epidemic, before medical measures for this emerging infectious disease were in place, the Outpatient Clinic received a significant amount of inquiries, reflecting the prevailing social turmoil. During the second wave, inquiries did not increase because a proper system of medical care was in place in hospitals and communities. Therefore, in the early stages of an emerging infectious disease, relevant information needs to be quickly consolidated and it needs to be linked to measures that are appropriate to the situation.